Pengaruh time pressure, resiko audit, locus of control, dan turnover intentions terhadap penghentian prematur atas prosedur audit (studi empiris pada kantor akuntan publik di pekanbaru, padang, jambi dan batam) - Anita, Yesy Tria; Kurnia, Pipin; ', Yusralaini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research aimed to analyze the time pressure, the risk of audit, the external locus of control, and turnover intentions to premature Sign-off of audit procedure. The respondent of this research was the auditor working in Public Accountant Firms in Pekanbaru, Padang, Jambi dan Batam. The method of collecting data in the research was survey method with the questionnaire instrument. The data usage in this research was primary data collecting through the questionnaires. The questionnaires proccesed were totaled as many as 67 questionnaires from 85 questionnaires diffused.According to the data quality consisted of he validity test, the reliability test and the normality test indicated that all variables could be valid, reliable, and normal so that for the next, the items of every variable concept was appropriately usd as an indicator.The result of this research indicated that the audit risk variable and turnover intentions have significanly influence to premature sign-off of audit procedure. Whilst the time pressure variable and the external locus of control don’t have significantly influence to premature sign-off of audit procedure.Keywords: Premature Sign-Off of Audit Procedure, Time Pressure, Audit risk, Locus of Control, and Turnover Intentions.